Peningkatan Keterampilan Proses Sains Mahasiswa melalui Percobaan Identifikasi Keberadaan Senyawa dalam Praktikum Kimia Analitik - Friska Juliana Purba; Chatrina Yohana Sihombing; Marchella Inabuy (Diligentia: Journal of Theology and Christian Education, 2026)
The purpose of this study is to improve students' science process skills (SPS) by applying the experimental approach in a guided practical method in the Analytical Chemistry Practical course. The study uses the Classroom Action Research (PTK) method, which is carried out in two cycles, each of which includes the planning, action, observation, and reflection stages. The study involved 23 students. Data collection techniques include tests and non-tests, such as pre- and post-tests, laboratory reports, and observation sheets based on science process skills. The data was analyzed using quantitative descriptive methods. The results of the study showed an increase in students' science process skills from cycle I to cycle II. The observation skill increased from an average score of 2.8 (70%) to 3.3 (82.5%) with a very good category. The measurement skill increased from an average score of 2.9 (72.5%) to 3.1 (77.5%) in the good category. The experimental skill was in the excellent category since the first cycle (82.5%) and remained stable in the second cycle. The communication skill increased from an average score of 2.8 (70%) to 3.1 (75.5%) in the good category. Based on these results, it can be concluded that the implementation of the laboratory method with a guided experimental approach supported by a laboratory manual is effective in improving students' science process skills, particularly in the areas of observation, measurement, and scientific communication in analytical chemistry education.